Performance Comparison of Three Algorithms for Two-Channel Sinewave Parameter Estimation: Seven Parameter Sine Fit, Ellipse Fit, Spectral Sinc Fit - Ramos, Pedro M. (2010)
The comparison of three different algorithms for the estimation of parameters of two sine signals with common frequency is presented. The algorithms are the ellipse fit, the seven parameter sine fit and the spectral sinc fit. The comparison includes signal to noise ratio analysis, amplitude analysis and phase difference analysis.